IMPROVEMENT OF DENTAL AND ORAL HEALTH BY CADERIZATION OF JUNIOR DENTISTS - Sandy Christiono; Rizki Amalina; Prima Agusmawanti (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Dental caries is still an unresolved problem. One method for the prevention of dental caries is the counselling method. Caderization is a long-term educational process for optimizing the potential of cadres by transferring and instilling specific values so that later it will produce strong cadres. Junior dentists meet the criteria and have been trained to participate in efforts to maintain and improve health for themselves, friends, family and the environment. The purpose of a junior dentist is to become drivers of healthy living at school, at home, and in their environment to help themselves, fellow students and others live healthy lives. Method: Making counselling media consisting of posters for counselling, models of teeth and toothbrushes, counselling videos about dental health delivered by junior dentists and conducting questionnaires for students' understanding levels. Data analyzed using descriptive statisticsResult: The results of the research in filling out the questionnaire after the students saw and listened to the junior dentist educational video found that 81.3% brushed their teeth twice a day, 59.4% answered that sweet foods caused cavities, 71.9% responded correctly that cavities if not treated will cause swelling, 90.6% answered incorrectly that teeth were only left alone if they had cavities and 93.8% answered how to maintain oral hygiene by brushing their teeth properlyConclusion: There is an increased understanding of dental and oral health